Optical properties of CdS and PbS nanocrystals adsorbed on silica nanoparticles - Yermolayeva, Yu.V.; Matveevskaya, N.A.; Semynozhenko, V.P.; Tolmachev, A.V. (Functional Materials, 2006)
The adsorption mechanism of CdS and PbS semiconductor nanocrystals on the surface of spherical silica particles has been investigated. The presence of quantum size effects in the "core-shell" heteronanostructures with dielectric SiO₂ core and semiconductor shell consisting of nanocrystals has been established. Influence of the core size and a degree of its covering with CdS, PbS nanocrystals on optical properties of heteronanostructures has been shown.